De deur - Simenon, Georges, 1903-1989; Romijn, K. H. (Utrecht : A. W. Bruna & Zoon, 1963)
De man-vrouw-verhouding komt regelmatig aan bod in het werk van Simenon: ook deze roman gaat over dergelijke relatie.